To What Extent Do Online News Platforms Frame Environmental Issues? A Content News Analysis In Indonesia's Dompu Maize Development Program - Wicaksono, Baskoro; Rahmat, Al Fauzi; Rahmanto, Fajar; Rafi, M.; Dávid, Lóránt Dénes (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2025)
This article examines how online news frames environmental issues in the corn development program in Dompu, West Nusa Tenggara, Indonesia. Furthermore, this article uses qualitative-exploratory research to analyze the news content with the analytical knife of Robert M. Entmen's framing model. Then, the data analysis tool uses NVivo 12 Plus to code the data and distribute terms and words that correlate with the framing of online news. The findings showed that certain aspects of the maize development program were more prominent, in general, the national online media emphasized elements of “make moral judgment” and “treatment recommendation”. In contrast, the local online media emphasized “define problem” and “diagnose cause”. Both online media explicitly instructed how environmental issues in Dompu Regency are important for environmental journalists. Thus, this implies differences in framing between national and local online media, and illustrates that environmental journalists have an important role in framing environmental issues.Keyword: Media framing, Online news, Environment issues, Corn program, Dompu. ABSTRAKArtikel ini meneliti bagaimana berita online membingkai isu lingkungan dalam program pengembangan jagung di Dompu, Nusa Tenggara Barat, Indonesia. Lebih lanjut, artikel ini menggunakan penelitian kualitatif-eksploratif untuk menganalisis konten berita dengan pisau analisis model framing Robert M. Entmen. Kemudian, alat analisis data menggunakan NVivo 12 Plus untuk mengkodekan data dan mendistribusikan istilah dan kata-kata yang berkorelasi dengan pembingkaian berita online. Temuan penelitian menunjukkan bahwa aspek-aspek tertentu dari program pengembangan jagung lebih menonjol, secara umum, media daring nasional menekankan unsur “make moral judgment” dan juga “treatment recommendation”. Sebaliknya, media daring lokal menekankan pada unsur “define problem” dan “diagnose cause”. Kedua media daring tersebut secara eksplisit menginstruksikan bagaimana isu lingkungan di Kabupaten Dompu menjadi penting bagi jurnalis lingkungan. Dengan demikian, penelitian ini menyiratkan adanya perbedaan pembingkaian antara media daring nasional dan lokal, dan menggambarkan bahwa jurnalis lingkungan memiliki peran penting dalam membingkai isu-isu lingkunganKata Kunci: Pembingkaian media, Berita online, Isu lingkungan, Program jagung, Dompu.